(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
• Anderson, G. (1995). Cognitive Psychology and Its Implications. New York: Freeman. • Buck, G. (2001). Assessing Listening. Cambridge: Cambridge University Press. • Kintsch, W. (1998). Comprehension: A Paradigm for Cognition. Cambridge: Cambridge University Press. • Mendelsohn, D. J. (1994). Learning to Listen: A Practical Guide to Listening Comprehension Activities. San Diego: Dominie Press. • Richards, J. C., & Renandya, W. A. (2002). Methodology in Language Teaching: An Anthology of Current Practice. Cambridge: Cambridge University Press. • Vandergrift, L., & Goh, C. C. M. (2012). Teaching and Learning Second Language Listening: Metacognition in Action. New York: Routledge. • Yunusova, Z. Z. (2022). LISTENING COMPREHENSION IS AN INTEGRAL PART OF LANGUAGE LEARNING AND ITS GENERAL PRINCIPLES. Oriental renaissance: Innovative, educational, natural and social sciences, 2(Special Issue 20), 508-514. • Yunusova, Z. (2024). Challenges and Opportunities in Teaching English to Journalism Students. Excellencia: International Multi-Disciplinary Journal of Education (2994-9521), 2(6), 339-341. • Zokirova, Z. (2022). The Role Of Listening In Language Acquisition; The Challenges & Strategies In Teaching Listening. Oriental renaissance: Innovative, educational, natural and social sciences, 2(Special Issue 20), 789-793.